TvLEGU-1 and TvLEGU-2 biomarkers for trichomoniasis are legumain-like cysteine peptidases secreted in vitro in a time-dependent manner - Euceda-Padilla, Esly Alejandra; Mateo-Cruz, Miriam Guadalupe; Ortega-López, Jaime; Arroyo, Rossana (Frontiers in Parasitology, 2025)
Trichomonas vaginalis is the causative agent of trichomoniasis, the most prevalent neglected parasitic sexually transmitted infection worldwide. Cysteine peptidases (CPs) are the most abundant proteins in the parasite degradome. Some CPs are virulence factors involved in trichomonal pathogenesis, cytoadherence, hemolysis, and cytotoxicity. Few are immunogenic and are found in the vaginal secretions of patients with trichomoniasis. Legumains are CPs of the C13 family of clan CD. T. vaginalis has 10 genes encoding legumain-like peptidases, and TvLEGU-1 and TvLEGU-2 have been characterized. Both are immunogenic and found in the vaginal secretions of patients with trichomoniasis that could be considered as potential biomarkers. Thus, our goal was to evaluate the effects of glucose on the proteolytic activity and secretion processes of TvLEGU-1 and TvLEGU-2. We performed in vitro secretion assays using different glucose concentrations, examined the presence and proteolytic activity of secreted legumains by Western blot and spectrofluorometry assays, and analyzed the localization of TvLEGU-1 and TvLEGU-2 in the parasites by indirect immunofluorescence. Our results show that TvLEGU-1 and TvLEGU-2 were secreted in vitro in a time-dependent manner and had legumain-like proteolytic activity that could contribute to parasite pathogenesis, supporting their relevance during infection and potential as trichomoniasis biomarkers.